Understanding Neuromuscular Health and Disease: Advances in Genetics, Omics, and Molecular Function - Duddy, William; Duguez, Stephanie (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This compilation focuses on recent advances in the molecular and cellular understandingof neuromuscular biology, and the treatment of neuromuscular disease.These advances are at the forefront of modern molecular methodologies, oftenintegrating across wet-lab cell and tissue models, dry-lab computational approaches,and clinical studies. The continuing development and application ofmultiomics methods offer particular challenges and opportunities in the field,not least in the potential for personalized medicine.